2020
DOI: 10.1002/hed.26421
|View full text |Cite
|
Sign up to set email alerts
|

Simple and complex carotid paragangliomas. Three decades of experience and literature review

Abstract: Background: Carotid paragangliomas are rare tumors. They are usually unique, non-secreting, resectable, and benign. However, additional rare cases of complex tumors (bilateral, secretory, nonresectable, or malignant) complicate the management and final outcomes. Methods: Records of paragangliomas from our hospital are reviewed. Criteria defining complex paragangliomas have been previously defined. These are compared with those of the simple group. Results: Fifty patients, two groups: simple (n = 39) and comple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 66 publications
0
7
0
1
Order By: Relevance
“…We demonstrated that surgical treatment without preoperative embolization is safe and effective even in large tumors. [30] 2016 47 45 (34-56) 33% 53% 14% 18% 6.4% 0% Lamblin et al [31] 2011 54 49 (38.2-57.7) 31.2% 46.3% 22.2% 47.6% 5.6% 0% Metheetrairut et al [21] 2015 38 36.9 (15-59) 22.5% 35% 42.5% 20% 5% 0% Fruhmann et al [15] 2013 50 54.5 (17-80) 20.6% 44.4% 34.9% 20.6% 2% 0% Torrealba et al [32] 2016 30 45.5 (18-75) 16.7% 63.3% 20% 23% 0% 0% Lozano et al [33] 2020 50 60.3 (33-78) 18% 16.3% 2% 6% Zhang et al [34] 2018 29 46 27.6% 55.2% 17.2% 27.6% 0% 0%…”
Section: Discussionmentioning
confidence: 99%
“…We demonstrated that surgical treatment without preoperative embolization is safe and effective even in large tumors. [30] 2016 47 45 (34-56) 33% 53% 14% 18% 6.4% 0% Lamblin et al [31] 2011 54 49 (38.2-57.7) 31.2% 46.3% 22.2% 47.6% 5.6% 0% Metheetrairut et al [21] 2015 38 36.9 (15-59) 22.5% 35% 42.5% 20% 5% 0% Fruhmann et al [15] 2013 50 54.5 (17-80) 20.6% 44.4% 34.9% 20.6% 2% 0% Torrealba et al [32] 2016 30 45.5 (18-75) 16.7% 63.3% 20% 23% 0% 0% Lozano et al [33] 2020 50 60.3 (33-78) 18% 16.3% 2% 6% Zhang et al [34] 2018 29 46 27.6% 55.2% 17.2% 27.6% 0% 0%…”
Section: Discussionmentioning
confidence: 99%
“…95,96 Surgery remains the most common strategy for managing CBTs. 8,9,48,98,99 It is associated with long-term control greater than 95%. 48,98 The Shamblin classification has long been used to predict operative morbidity and mortality in CBTs.…”
Section: Isolated Cbtsmentioning
confidence: 99%
“…Among these articles, 20 (158 patients) included 5 or more patients (Table 1) 18–39 and were considered for the proportion MA. The remaining 112 studies (179 patients), represented by case reports or case series with <5 patients, are reported in Table S1 3,40–152 …”
Section: Resultsmentioning
confidence: 99%